Analisis Saluran Kabel Tegangan Rendah di Kampus Universitas Pendidikan Indonesia - Gilar Algifari; I Wayan Ratnata; Elih Mulyana (ELECTRANS, 2016)
Low-voltage distribution cable has important role in electric power distribution system. This study aimed to find out power distribution network, drop voltage, losses, and Rupiah loss on low-voltage distribution cable in Indonesia University of Education (UPI), Bandung. UPI has their own electrical substation, so low voltage electricity managed by themselves. This research is conducted because of researcher’s interest in analyzing reliability of power distribution in UPI. Data was derived from measurement and calculation of load current from every substation which flows to switchgear in every building. Based on the result, the calculation is continued to find out the magnitude of voltage drop, losses (watt), and Rupiah loss. The magnitude of drop voltage and power losses in UPI’s low voltage distribution cable network are very good based on the value which is lower than assigned minimun limit by PT. PLN; +5% and -10%. In Rupiah, UPI losses Rp.398.573,- in January 2014.